Risk factors for fluorouracil-induced cardiotoxicity in patients with gastrointestinal tumor - Wu, Yuting; Lv, Chen; Li, Jindong; Ma, Ying; Zhu, Xiaoli (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo explore the risk factors for cardiotoxicity in patients with gastrointestinal (GI) tumors treated with fluorouracil drugs.MethodsThis study included patients with GI tumors who received fluorouracil at our hospital between January 2018 and April 2022. The demographic and clinical characteristics were collected. The risk factors associated with the cardiotoxicity of fluorouracil were explored using multivariable logistic regression.ResultsA total of 300 patients were finally included and divided into the cardiotoxicity (n = 81) and non-cardiotoxicity groups (n = 219). The occurrence of fluorouracil-induced cardiotoxicity was higher in patients with hypertension, hyperlipidemia, diabetes mellitus, older age, those treated with capecitabine, and combined radiotherapy. The multivariable logistic regression showed that treatment with capecitabine, history of hyperlipidemia, history of diabetes, older age, and combined radiotherapy were independent risk factors for the cardiotoxicity of fluorouracil.ConclusionHyperlipidemia, diabetes, older age, treatment with capecitabine, and adjuvant radiotherapy might be independent risk factors for the cardiotoxicity of fluorouracil in patients with GI tumors.